2021
DOI: 10.3389/fnmol.2021.758915
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-brain Natriuretic Peptide Is Associated With Hemorrhagic Transformation and Poor Outcomes in Patients With Stroke Treated With Intravenous Thrombolysis

Abstract: Background: N-terminal pro-brain natriuretic peptide (NT-proBNP) levels are a promising biomarker for predicting stroke outcomes; however, their prognostic validity is not well-understood in patients who have undergone intravenous thrombolysis. This study was designed to evaluate the prognostic value of NT-proBNP levels in patients with acute ischemic stroke treated with intravenous thrombolysis.Methods: Patients with ischemic stroke who underwent intravenous thrombolysis between April 2015 and December 2020 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Finally, NT-proBNP is an inactive fragment derived from the cleavage of BNP [ 35 ]. In line with earlier studies [ 36 38 ], our findings showed that NT-proBNP level was independently associated with HT in patients with stroke who had received IVT. One possible explanation was that HT exacerbated the brain damage caused by ischemic stroke [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, NT-proBNP is an inactive fragment derived from the cleavage of BNP [ 35 ]. In line with earlier studies [ 36 38 ], our findings showed that NT-proBNP level was independently associated with HT in patients with stroke who had received IVT. One possible explanation was that HT exacerbated the brain damage caused by ischemic stroke [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, elevated NT-ProBNP is the strongest independent predictor of long-term adverse clinical outcomes in patients with acute ischemic stroke ( Yang et al, 2018 ). Recent studies have shown that NT-proBNP is associated with bleeding transformation and poor prognosis in stroke patients treated with intravenous thrombolytic therapy ( Zhang et al, 2021 ). In a preliminary single-center study, 4.9% of AIS patients without pre-existing cardiovascular comorbidities developed heart failure during hospitalization, where only one third of heart failure is caused by acute myocardial infarction after stroke ( Micheli et al, 2012 ).…”
Section: Cardiac Dysfunctionmentioning
confidence: 99%
“…Early prediction is crucial for effective doctor-patient communication and the timely implementation of preventive measures to reduce the incidence of END. Many indicators, such as aquaporin-4 levels or active N-terminal pro-brain natriuretic peptide levels, are typically obtained post-intravenous thrombolysis and are seldom measured in emergency settings [9][10][11] In many studies, it is noted that large artery disease 9,13 , coupled with a low ASPECTS 14,15 , can contribute to the occurrence of END. Large arterial lesions result in extensive ischemic tissue and potentially a signi cant ischemic penumbra.…”
Section: Discussionmentioning
confidence: 99%